cAMP/PKA/CREB/GLT1 signaling involved in the antidepressant-like effects of phosphodiesterase 4D inhibitor (GEBR-7b) in rats - Liu X; Guo H; Sayed MDSM; Lu Y; Yang T; Zhou D; Chen Z; Wang H; Wang C; Xu J (Neuropsychiatric Disease and Treatment)
Xu Liu,1,2,* Haibiao Guo,1,* Mohammad Daud SOM Sayed,3,4,* Yang Lu,3,4,* Ting Yang,5,* Dongsheng Zhou,6 Zhongming Chen,6 Haitao Wang,1 Chuang Wang,3,4 Jiangping Xu1 1Guangdong Provincial Key Laboratory of New Drug Screening, School of Pharmaceutical Sciences, Southern Medical University, Guangzhou, Guangdong, 2Department of Pharmacy, General Hospital of Chinese People’s Armed Police Forces, Beijing, 3Ningbo Key Laboratory of Behavioral Neuroscience, 4Zhejiang Provincial Key Laboratory of Pathophysiology, School of Medicine, Ningbo University, Ningbo, Zhejiang, 5Department of Pediatrics, The Affiliated Hospital of Ningbo University, Ningbo, Zhejiang, 6Department of Geriatric Psychiatry, Ningbo Kangning Hospital, Ningbo, Zhejiang, People’s Republic of China *These authors contributed equally to this work Objectives: GEBR-7b, a potential phosphodiesterase 4D inhibitor, has been shown to have memory-enhancing effects in rodents. However, it is still unknown whether GEBR-7b also has the antidepressant-like effects in rats. Herein, we examined the potential of GEBR-7b to attenuate depression-like behaviors in the rat model of depression induced by chronic unpredictable stress (CUS). Next, we also investigated the alterations of cyclic adenosine monophosphate (cAMP), protein kinase A (PKA) catalytic subunit (PKAca), cAMP response element-binding (CREB), and glutamate transporter 1 (GLT1) levels produced by GEBR-7b in the rats model of depression.Methods: Effects of GEBR-7b on CUS (35 days)-induced depression-like behaviors were examined by measuring immobility time in the forced swimming test (FST). Hippocampal cAMP levels were examined by enzyme-linked immunosorbent assay, whereas PKAca, phosphorylation of CREB (pCREB), CREB, and GLT1 in the hippocampus of rats were subjected to Western blot analysis.Results: CUS exposure caused a depression-like behavior evidenced by the increased immobility time in FST. Depression-like behavior induced by CUS was accompanied by a significant increased GLT, decreased cAMP, PKAca, pCREB activities in hippocampus. However, repeated GEBR-7b administration significantly reversed CUS-induced depression-like behavior and changes of cAMP/PKA/CREB/GLT1 signaling. No alteration was observed in locomotor activity in open field test.Conclusion: These findings indicate that GEBR-7b reversed the depression-like behaviors induced by CUS in rats, which is at least in part mediated by modulating cAMP, PKAca, pCREB, and GLT1 levels in the hippocampus of rats, supporting its neuroprotective potential against behavioral and biochemical dysfunctions induced by CUS. Keywords: phosphodiesterase 4D, GEBR-7b, cyclic adenosine monophosphate, protein kinase Aca, cAMP response element-binding protein, phosphorylation of CREB, glutamate transporter 1